Isotopic evidence for bioaccumulation of aerosol lead in fish and wildlife of western Canada. (1st June 2022) - Chételat, John; Cousens, Brian; Hebert, Craig E.; Jung, Thomas S.; Mundy, Lukas; Thomas, Philippe J.; Zhang, Shuangquan
Abstract: Lead (Pb) is a toxic element which is released as a result of anthropogenic activities, and Pb stable isotope ratios provide a means to distinguish sources and transport pathways in receiving environments. In this study, isotopes of bioaccumulated Pb ( 204 Pb, 206 Pb, 207 Pb, 208 Pb) were examined for diverse terrestrial and aquatic biota from three areas in western Canada: (a) otter, marten, gulls, terns, and wood frogs in the Alberta Oil Sands Region (AOSR), (b) fish, plankton, and gulls of Great Slave Lake (Yellowknife, Northwest Territories), and (c) wolverine from the Yukon. Aquatic and terrestrial biota from different habitats and a broad geographic area showed a remarkable similarity in their Pb isotope composition (grand mean ± 1 standard deviation: 206 Pb/ 207 Pb = 1.189 ± 0.007, 208 Pb/ 207 Pb = 2.435 ± 0.009, n  = 116). Comparisons with Pb isotope ratios of local sources and environmental receptors showed that values in biota were most similar to those of atmospheric Pb, either measured in local aerosols influenced by industrial activities in the AOSR or in lichens (an aerosol proxy) near Yellowknife and in the Yukon. Biotic Pb isotope ratios were different from those of local geogenic Pb. Although the Pb isotope measurements could not unambiguously identify the specific anthropogenic sources of atmospheric Pb in biota, initial evidence points to the importance of fossil fuels currently used in transportation and power generation. Further research should characterize bioavailable chemical species of Pb in aerosols and important emission sources in western Canada. Graphical abstract: Image 1 Highlights: Pb isotope ratios were strikingly similar in diverse animals from western Canada. The bioaccumulated Pb originated primarily from atmospheric aerosols. Natural geogenic sources contributed little to bioaccumulated Pb. Pb isotopes suggest aerosol Pb is highly bioavailable. Fossil fuels may be important sources of bioavailable Pb to fish and wildlife.